The lateral load resistance of unclassified cross-laminated timber walls: Experimental tests and theoretical approach. (1st July 2018) - Wadi, H.; Amziane, S.; Taazount, M.
Highlights: Racking performance of timber frame wall (OSB) and CLT walls has been conducted. Against lateral load, CLT walls is more resistant than OSB panel design. The number of internal rotational moments that are created in each shear plane of intersection in the wall is a key parameter. An analytical model evaluate the internal forces on each fastener. Abstract: This paper focuses mainly on the mechanical behaviour of unclassified cross-laminated timber walls under lateral loading (seismic and wind loads). Unclassified wooden planks were used to construct the wall unit with an odd number of layers (three) for each wall, with the planks in each layer in a perpendicular relative orientation. In this research, an experimental study of large-scale timber walls was carried out with a view to determining the lateral load resistance. Diagonal struts, under tension and compression were employed on the cross-laminated walls to investigate the effects of these elements on the lateral resistance of the wall. A theoretical approach has been developed to describe the overall behaviour of the cross-laminated wall and to investigate the internal forces on the fasteners. The present work is then compared to Oriented Strand Board (OSB) panel designs. Based on the data and results obtained from the experimental tests, this study confirms, firstly, that cross-laminated walls without a diagonal strut have approximately double the horizontal strength of (OSB) panels, secondly, that diagonal strut significantly increases the lateral load resistance of cross-laminated walls, particularly under compression conditions, and thirdly, the proposed theoretical approach shows similar performance to the average experimental test up to 100 mm of overall lateral displacement of cross-laminated timber wall.